Prevalence and Severity of Plaque-Induced Gingivitis in Three Latin American Cities: Mexico City-Mexico, Great Metropolitan Area-Costa Rica and Bogota-Colombia - Murillo DDS, MDSc, Gina (2018)
Plaque-induced gingivitis is the most common form of periodontal disease and can affect 100% of the population. Gingivitis prevalence in Latin American population is not well documented, therefore the aim of this study was to determine the prevalence and severity of plaque-induced gingivitis in adult populations of three Latin American cities.   Methods: This cross sectional multicenter study included 1650 participants, 550 from the Great Metropolitan Area of Costa Rica (GAM), 550 from Mexico City, Mexico (CDMX) and 550 from Bogota City, Colombia (BC). Subjects completed a questionnaire about their medical history and oral hygiene. Clinical assessment included recording of missing teeth, visible plaque index, calculus recording and gingival index (GI, Loe-Silness index).  Results: Average GI was 1.36. No statistical difference was found between GAM (1.45) and BC (1.48); however, GI in CDMX was significantly lower (1.16). Average gingival bleeding on probing was 43%. Total plaque index was 0.76 showing the highest accumulation at interproximal sites (p=0.0001). A positive correlation was found between plaque and gingivitis (r=0.59). Dental calculus was present in at least one of the 18 evaluated sites per subject with no statistical difference between cities. There was no statistical difference in GI between smokers, former smokers and non- smokers.  Conclusion: Gingivitis prevalence was 99.6%. Moderate Gingivitis was the predominant form, with no statistically significant difference between cities or gender. Dental plaque accumulation was the most important risk factor associated with the establishment of the disease.